The Impact of Green Marketing On Consumers’ Green Purchase Intention In Fast Fashion Industry: Case Of Uniqlo Indonesia (Journal of Business and Management, 2022)
Many fashion brands are implementing “fast fashion” strategies, resulting in negative effects to the environment where the waste pollutes and degrades the natural environment and surrounding ecosystem. Consumers in Indonesia are growing awareness regarding these environmental issues caused by the fashion industry. For countermeasure, fast fashion brands have been including green aspect into their marketing strategy. In this research, the author aims to examine how green marketing will influence the green purchase intention among consumers. This research is conducted through a qualitative approach by interviewing 7 consumers, and a quantitative approach by using online surveys to collect insights from 311 consumers of UNIQLO Indonesia who have purchased product(s) from UNIQLO Indonesia at least once within the past year. The researcher utilizes open coding to analyze the result of the interview, and uses PLS-SEM to analyze the result of the survey. The result shows that green marketing will influence consumers’ green purchase intention through partial mediation of green knowledge, green attitude, and green brand image. Therefore, green marketing is an important marketing strategy to be considered by fast fashion brands because it can encourage consumers’ purchase intention.Keywords: Green Marketing; Green Purchase Intention; UNIQLO Indonesia; PLS-SEM.